2008
DOI: 10.1007/s12155-008-9021-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Two-Stage Dilute Acid Pretreatment on the Structure and Composition of Lignin and Cellulose in Loblolly Pine

Abstract: A standard two-step dilute sulfuric acid pretreatment was performed on Loblolly pine to enhance the overall efficiency of enzymatic deconstruction of woody biomass to monomeric sugars. The structure of milled wood lignin and cellulose isolated from the untreated and acid-treated biomass was studied in detail. Solid-state 13 C NMR spectroscopy coupled with line shape analyses has been employed to elucidate cellulose crystallinity and ultrastructure. The results indicate an increase in the degree of crystallinit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
142
2
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(153 citation statements)
references
References 58 publications
6
142
2
3
Order By: Relevance
“…It has been observed (Foston and Ragauskas 2010) that the relative amount of the cellulose Ia form decreases while the relative amount of Ib allomorph increases with the duration of the process. A similar result has been reported for pretreatment of loblolly pines (Sannigrahi et al 2008). The Ia allomorph is used industrially more often than Ib because of its higher reactivity towards acetylation (Sassi et al 2000).…”
Section: Introductionsupporting
confidence: 84%
“…It has been observed (Foston and Ragauskas 2010) that the relative amount of the cellulose Ia form decreases while the relative amount of Ib allomorph increases with the duration of the process. A similar result has been reported for pretreatment of loblolly pines (Sannigrahi et al 2008). The Ia allomorph is used industrially more often than Ib because of its higher reactivity towards acetylation (Sassi et al 2000).…”
Section: Introductionsupporting
confidence: 84%
“…More precisely, line shape analysis based on a nonlinear least squares fitting analysis has been performed on this area, and it was found that the signals at 80 to 86 ppm are attributable to C-4 carbons at the accessible fibril surface and inaccessible fibril surface (Larsson et al 1999). In addition, the ratio of the area in the 86 to 92 ppm region to the total peak area in these two regions is designated as the crystallinity index (Sannigrahi et al 2008).…”
Section: Cc50mentioning
confidence: 99%
“…The spectrum obtained is shown in Fig. 4, and previously assigned signals from the literature (Sanningrahi et al 2008;Pu et al 2006) were used to assign the observed resonance. Between 80 and 100 ppm, no signals were observed, indicating low sugar content in the extracted lignin.…”
Section: Ethanol Organosolv Lignin (Eol) Recovery and Characterizationmentioning
confidence: 99%